2021
DOI: 10.1371/journal.pone.0247996
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mobility homophily in Stockholm based on social network data

Abstract: We present a novel metric for measuring relative connection between parts of a city using geotagged Twitter data as a proxy for co-occurrence of city residents. We find that socioeconomic similarity is a significant predictor of this connectivity metric, which we call “linkage strength”: neighborhoods that are similar to one another in terms of residents’ median income, education level, and (to a lesser extent) immigration history are more strongly connected in terms of the of people who spend time there, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Unlike previous studies 23 , 35 , we do not observe universal assortativity patterns over all cities in these networks. In some of the cities, such as Detroit, the strong diagonal component features strong segregation patterns, meaning that people tend to commute to neighborhoods with similar annual household incomes as their home neighborhood, and they tend to form social ties with people living in neighborhoods with similar income, as also found in 24 . In cities like Boston, patterns of mobility and online social ties are less assortative with higher likelihood for diverse, off-diagonal connections.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Unlike previous studies 23 , 35 , we do not observe universal assortativity patterns over all cities in these networks. In some of the cities, such as Detroit, the strong diagonal component features strong segregation patterns, meaning that people tend to commute to neighborhoods with similar annual household incomes as their home neighborhood, and they tend to form social ties with people living in neighborhoods with similar income, as also found in 24 . In cities like Boston, patterns of mobility and online social ties are less assortative with higher likelihood for diverse, off-diagonal connections.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, spatial segregation by income also fragments social networks, which can hinder progress and can deepen inequalities 16 20 . Given the importance of this problem, a growing community has investigated the patterns of mobility in cities to better understand mixing potentials across disparate and diverse neighborhoods 21 24 , which may increase economic prosperity 25 . Yet, less is known whether mobility mixing has any imprint on the social connections of people.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous studies (Dong et al 2020;Morales et al 2019), we do not observe universal assortativity patterns over all cities in these networks. In some of the cities, such as Detroit, the strong diagonal component features strong segregation patterns, meaning that people tend to commute to neighborhoods with similar annual household incomes as their home neighborhood, and they tend to form social ties with people living in neighborhoods with similar income, as also found in (Heine et al 2021). In cities like Boston, patterns of mobility and online social ties are less assortative with higher likelihood for diverse, off-diagonal connections.…”
Section: Resultsmentioning
confidence: 80%
“…For instance, the theory of homophily states that people who share characteristics (e.g., age, sexuality, hobbies) tend to connect and interact with each other online and to congregate offline ("birds of a feather flock together"; e.g., McPherson et al, 2001). Inspired by this theory, Heine et al (2021) used geotagged tweets of residents in Stockholm to analyze how their movements around the city connected them to different neighborhoods. The authors found that the socioeconomic similarity of neighborhoods in Stockholm (i.e., similarity in residents' income, education level, and immigration history) could predict how individuals moved through those areas (i.e., residents of socioeconomically similar neighborhoods were likely to adopt similar movement patterns throughout the city).…”
Section: How the Use Of Mobilities Data Has Been Informed By Psycholo...mentioning
confidence: 99%